Cobalt bismuth oxide with cobalt(II/III) as a new stable peroxymonosulfate activator for effective degradation, mineralization, and detoxification of diclofenac in water. (10th September 2022) - Zhao, Wei; Duan, Zhiyao; Zheng, Zheng; Li, Bo
Abstract: Peroxymonosulfate-based advanced oxidation process (PMS-AOPs) is one of most effective approaches for eliminating emerging organic pollutants (EOPs). To develop high-performance and stable PMS activators is the key to the further development of PMS-AOPs. Cobalt-based catalysts have been proved to be the excellent PMS activators. Here, cobalt bismuth oxide (Bi7.53 Co0.47 O11.92 ) prepared by facile one-step calcination method was employed as the new PMS activator. As expected, diclofenac (DCF), one kind of EOPs, were quickly decomposed and even mineralization by the Bi7.53 Co0.47 O11.92 activated PMS system. Within 10 min of reaction, 100% degradation efficiency and 82.1% mineralization rate were achieved. The toxicity of degraded products was assessed to be much lower than pristine DCF. Moreover, six-cycle experiments verified the good reusability of Bi7.53 Co0.47 O11.92 . This work contributes to develop new stable and high-efficiency PMS heterogeneous activators, being beneficial to build high-performance PMS-AOPs for EOPs treatment. Graphical abstract: Image 1 Highlights: Cobalt bismuth oxide with stable surface Co active site was synthesized. Efficient mineralization and detoxification of DCF was achieved. The stable reusability of cobalt bismuth oxide in activating PMS was determined. Superoxide radicals were mainly responsible for the quick decomposition of DCF.